New tests for symmetry - Maniušis, Vytautas (Lietuvos matematikos rinkinys, 2001)
A new class of tests for symmetry of random variables is considered. This class is based on the empirical characteristic function. Tests from this class are compared with the classical Sign test using graphical display of P values. It is easy to extend this approach to the multivariate case.